Effect of gestational age at first delivery and interpregnancy interval on the recurrence of clinical chorioamnionitisAJOG Global Reports at a Glance - Meryl M. Sperling, MD, MA; Lillian Sie, MPH; Stephanie A. Leonard, PhD, MS; Anna I. Girsen, PhD, MD; Henry C. Lee, MD; Ronald S. Gibbs, MD (Elsevier, 2022)
BACKGROUND: There is an increased odds of having a recurrence of clinical chorioamnionitis in patients with a diagnosis of clinical chorioamnionitis compared with those without clinical chorioamnionitis in a previous pregnancy. However, it is unclear how gestational age at delivery of the first pregnancy or interpregnancy interval may contribute to this increased risk. OBJECTIVE: This study aimed to evaluate how gestational age of delivery in a first pregnancy and interpregnancy interval affect the odds of recurrent clinical chorioamnionitis. STUDY DESIGN: Using maternally linked birth record files, Nulliparous patients from California with at least 2 consecutive deliveries between the gestational ages of 20 and 44 weeks from 2007 to 2012 were identified. The rates of clinical chorioamnionitis in the second pregnancy for patients with clinical chorioamnionitis vs those without clinical chorioamnionitis in the first pregnancy, stratified by the gestational age at delivery of the first pregnancy were determined. As a secondary analysis, the analysis by interpregnancy interval (<18 months vs ≥18 months) was stratified. Corresponding crude and adjusted odds ratios for each stratum were calculated to assess the association of clinical chorioamnionitis in the first and second pregnancies. RESULTS: Among 31,571 nulliparous patients with clinical chorioamnionitis in the first pregnancy, the frequency of clinical chorioamnionitis in the next pregnancy was 4.0% (1257 cases). This was in comparison with the 1.0% (9177 of 896,154) of nulliparous patients without clinical chorioamnionitis in the first pregnancy who were diagnosed with clinical chorioamnionitis in the next pregnancy (adjusted odds ratio, 2.78; 95% confidence interval, 2.61-2.96). The absolute frequency of recurrence was the highest (54 cases [8.2%]) in those who delivered at 20 to 24 weeks of gestation in the first pregnancy with the diagnosis of clinical chorioamnionitis (adjusted odds ratio, 1.76; 95% confidence interval, 1.25-2.48). For pregnancies delivered at term in the first pregnancy, the frequency of clinical chorioamnionitis in the next pregnancy was higher in those diagnosed with clinical chorioamnionitis in the first pregnancy than in those without clinical chorioamnionitis in the first pregnancy (4.0% vs 1.0%; adjusted odds ratio, 2.85; 95% confidence interval, 2.66-3.05). An interpregnancy interval of <18 months was not associated with increased odds of recurrent clinical chorioamnionitis. CONCLUSION: The odds of recurrence of clinical chorioamnionitis were the strongest when a patient delivered in the term to postterm period in the first pregnancy, with the absolute risk being the highest when the first pregnancy was delivered in the periviable period (20-24 weeks of gestation). The interpregnancy interval did not seem to modify the risk of recurrent clinical chorioamnionitis.